Digital learning: Perceptions of lecturers at a Technical Vocational Educational and Training college - Mbanga, N.; Mtembu, V.N. (South African Journal of Higher Education, 2020)
This study investigated the perceptions of Technical Vocational Education and Training College (TVET) lecturers towards digital learning (DL) at the College. The study adopted a mixed research methodology to investigate the phenomenon, and utilised exploratory research. The study was conducted among a population of 125 lecturers and management at the TVET College; both stratified and purposive sampling methods were employed to determine the participants of the study. With the exclusion criteria that required that participants should have knowledge or experience of digital learning, have been working with for the College for more than a year, and must have attended the digital learning workshop hosted by the college and organised by the digital learning service providers in May 2017, researchers ended up with a sample size of 75 participants. Questionnaires and interviews were the principal instruments for data collection. The quantitative data gathered was examined by utilising the Statistical Package for the Social Science (SPSS), version 24.0, while the qualitative data gathered were transcribed manually and analysed using thematic analysis. The findings revealed that TVET lecturers perceived digital learning as a conducive way to facilitate interactions and discussions between lecturers and learners, is convenient to use, facilitates and improves teaching and learning, and is user friendly. Moreover, the TVET lecturers’ perceptions indicated readiness and willingness to apply digital learning at the TVET College although infrastructure and systems in the college reflected non-readiness for effective roll out of digital learning. The study recommends that; institutional needs, instructor’s needs and learner’s needs be evaluated prior to the implementation of digital learning. It is also recommended that sufficient training be provided to all users prior to the full adoption of digital technology and that there is provision of complete infrastructure, including software and hardware, full access to the internet, IT manuals and reading and training materials as key requirements to achieve effective implementation of digital learning.